2016
DOI: 10.1002/syn.21941
|View full text |Cite
|
Sign up to set email alerts
|

l-DOPA-induced dyskinesia in Parkinson's disease: Are neuroinflammation and astrocytes key elements?

Abstract: Inflammation in Parkinson's disease (PD) is a new concept that has gained ground due to the potential of mitigating dopaminergic neuron death by decreasing inflammation. The solution to this question is likely to be complex. We propose here that the significance of inflammation in PD may go beyond the nigral cell death. The pathological process that underlies PD requires years to reach its full extent. A growing body of evidence has been accumulated on the presence of multiple inflammatory signs in the brain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 360 publications
(563 reference statements)
4
48
0
4
Order By: Relevance
“…In fact, during PD, inflammatory features have been found to be coupled with changes in astrocytes and microglia after long‐term l ‐dopa treatment. Thus, inflammation and abnormal glial function may play a crucial role in PD and LID induction progression . Similarly, it has been reported that glial activity is of critical importance during SD.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, during PD, inflammatory features have been found to be coupled with changes in astrocytes and microglia after long‐term l ‐dopa treatment. Thus, inflammation and abnormal glial function may play a crucial role in PD and LID induction progression . Similarly, it has been reported that glial activity is of critical importance during SD.…”
Section: Discussionmentioning
confidence: 82%
“…We cannot exclude that MB is acting throughout another mechanism besides inhibition of sGC or NOS. Non‐neuronal mechanisms, as neuroinflammation, were recently proposed to influence LID (Bortolanza et al ., ,b; Del‐Bel et al ., ; Mulas et al ., ; Carta et al ., ). MB is able to inhibit prostacyclin synthesis (Martin et al ., ) and to suppress pro‐inflammatory cytokines and microglial activation (Dibaj et al ., ; Fenn et al ., ; Xu et al ., ), which have been directly or indirectly related to LID (Barnum et al ., ; Bortolanza et al ., ,b; Dos‐Santos‐Pereira et al ., ; Mulas et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Astrocytes and microglia do not constitutively express iNOS but they express the enzyme in pathological conditions such as ischemia, trauma, neurotoxic and inflammatory damage. Several lines of evidence demonstrated that glial NO is involved in the pathophysiology of a variety of neurological diseases including demyelination …”
Section: Signaling Of Astroglial Inos and Neuroinflammationmentioning
confidence: 99%
“…Several lines of evidence demonstrated that glial NO is involved in the pathophysiology of a variety of neurological diseases including demyelination. [29][30][31] As the blood-brain barrier (BBB) normally restricts the access of immune cells from the blood, the brain is traditionally considered as an "immunologically privileged site". However, it is now known that immunological reactions occur in the CNS, particularly during brain inflammation, which differs from inflammation in the periphery because of the relative absence of leukocytes and antibodies.…”
Section: Signaling Of Astroglial Inos and Neuroinflammationmentioning
confidence: 99%